Pre-fermentative cold maceration, saignée, and various thermal treatments as options for modulating volatile aroma and phenol profiles of red wine. (1st June 2017) - Lukić, Igor; Budić-Leto, Irena; Bubola, Marijan; Damijanić, Kristijan; Staver, Mario
Highlights: Standard and several emerging red grape mash maceration techniques were studied. Pre-fermentation heating liquid fermentation produced more esters and anthocyanins. Post-fermentation heating produced more flavonoids, color intensity and hue. Cold pre-fermentation maceration wines had increased anthocyanin/tannin ratio. Calculated aroma and taste series successfully approximated wine sensory attributes. Abstract: The effects of six maceration treatments on volatile aroma and phenol composition of Teran red wine were studied: standard maceration (control C), cold pre-fermentation maceration (CPM), saignée (S), pre-fermentation heating with extended maceration (PHT) or juice fermentation (PHP), and post-fermentation heating (POH). PHP wine contained the highest amounts of esters, fatty acids and anthocyanins, and the lowest content of other phenols. Alternative treatments decreased higher alcohols in relation to control C. CPM treatment lowered the extraction of seed tannins, exhibited the highest acetaldehyde, ethyl acetate and C6 -compounds levels, and had increased ester levels in relation to control C. POH wine contained the highest concentration of total phenols, flavonoids, monomeric, oligomeric and polymeric flavanols, and color intensity and hue. S and PHT wines contained lower amount of total phenols, but higher than in C and CPM wines. The calculated Odor Activity Values were used to establish significant differences between the treatments.